DH Training in Spanish: Digital Humanities as an e-learning platform to teach between Spain and Latin America - Rio Riande, María Gimena del (2016)
#dariahTeach is developing open source, community-driven, source, high quality, multilingual teaching materials for the digital arts and humanities. Begun in January 2015 and running through June 2017, #dariahTeach is funded through an Erasmus + Strategic Partnership Grant. The #dariahTeach consortium has eight partners, coordinated by Maynooth University, Ireland. LINHD UNED is part of this initiative and is collaborating through the experience of Elena González Blanco and Gimena del Rio as experts in online distant teaching on Digital Humanities.